2017
DOI: 10.5252/z2017n2a4
|View full text |Cite
|
Sign up to set email alerts
|

The genusMercuriaBoeters, 1971 in France (Gastropoda: Caenogastropoda: Hydrobiidae). West-European Hydrobiidae, Part 13

Abstract: The Mercuria Boeters, 1971 species living in the coastal zones of France are reviewed. In the Atlantic zone the genus Mercuria comprises four species:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 15 publications
1
23
2
Order By: Relevance
“…All species were recovered as independent entities in our phylogenetic inference (Figure 2) and ABGD analyses, including the European species with an uncorrected p-distance of 7.7% between them. These findings contradict previous studies (Girardi 2004, Gargominy et al 2011, Boeters and Falkner 2017) in which the populations of M.emiliana studied by Boeters (1988) were synonymized with M.similis and the populations of M.emiliana described by Paladilhe (1866) were included within the genus Pseudamnicola Paulucci, 1878. Our molecular study revealed that sequences of M.emiliana available in GenBank (Table 1) were genetically distant from both the species M.similis and those of the genus Pseudamnicola (Table 2).…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…All species were recovered as independent entities in our phylogenetic inference (Figure 2) and ABGD analyses, including the European species with an uncorrected p-distance of 7.7% between them. These findings contradict previous studies (Girardi 2004, Gargominy et al 2011, Boeters and Falkner 2017) in which the populations of M.emiliana studied by Boeters (1988) were synonymized with M.similis and the populations of M.emiliana described by Paladilhe (1866) were included within the genus Pseudamnicola Paulucci, 1878. Our molecular study revealed that sequences of M.emiliana available in GenBank (Table 1) were genetically distant from both the species M.similis and those of the genus Pseudamnicola (Table 2).…”
Section: Discussioncontrasting
confidence: 82%
“…The gastropod genus Mercuria Boeters, 1971 (Truncatelloidea, Hydrobiidae) is widely distributed in continental aquatic systems of western Mediterranean territories and islands (Giusti 1979, Boeters 1988, Glöer et al 2010, Patzner and Glöer 2013, Boeters and Falkner 2017) and more rarely in those of the Atlantic coasts of North Africa (Glöer et al 2015) and Western Europe (Boeters 1988, Kadolsky 2011, Glöer et al 2015, Boeters and Falkner 2017) and Madeira (Glöer et al 2015). This genus currently comprises 26 species occurring mainly in lowland regions of North Africa (nine species; Glöer et al 2015), continental France (six species; Boeters and Falkner 2017), and the Iberian Peninsula and Balearic Islands (four species, Boeters 1988, Glöer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations